THE INFLUENCE OF USE AUDIO VISUAL MEDIA TO INCREASE THE DEVELOPMENT OF EARLY CHILDHOOD LANGUAGE - Sri Bintang Anshar Alim Thorifah; Khairul Umam (Universitas Muhammadiyah Ponorogo, 2019)
The problem in this research is the development of early childhood language that has not been expected. The research aim to determine the influence of use audio visual media to increase the development of early childhood language. The research methods used are experimental methods with pre-experimental design. The samples in this research were children aged 5-6 years, amounting to 41 children. The data collection techniques used are observations. Analysis of data in this research using simple linier regression tests. The results showed that there was a significant influence on the use of audio visual media against early childhood language skills. This means that the use of audio visual media in the learning process in early childhood can help to increase the development of early childhood language. Thus, the role of teacher is expected in the use of audio visual media to increase the development of early childhood language.